2011
DOI: 10.1007/s10529-011-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of glycoside hydrolase family 11 endoxylanase from Bacillus pumilus ARA

Abstract: An endoxylanase gene, xynA, was cloned from Bacillus pumilus ARA and expressed in Escherichia coli. The open reading frame of the xynA gene was 687 bp encoding a signal peptide and a mature xylanase with a molecular mass of 23 kDa. The enzyme was categorized as a glycosyl hydrolase family 11 member based on the sequence analysis of the putative catalytic domain. The recombinant XynA (Bpu XynA) was purified to homogeneity by Ni-NTA and ion exchange chromatography on DEAE-Sepharose FF. The enzyme exhibited highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Bioinformatic analysis of the spectra on the Mascot platform identified peptides belonging to the endo-1,4-β-xylanase of Bacillus sonorensis or uncultured bacteria with scores 304 and 101, respectively ( Table 2 ). The endo-1,4-β-xylanase is affiliated with glycosyl hydrolases [ 45 ] and is often found in bacteria of the genus Bacillus [ 12 , 14 16 , 18 21 , 23 , 26 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic analysis of the spectra on the Mascot platform identified peptides belonging to the endo-1,4-β-xylanase of Bacillus sonorensis or uncultured bacteria with scores 304 and 101, respectively ( Table 2 ). The endo-1,4-β-xylanase is affiliated with glycosyl hydrolases [ 45 ] and is often found in bacteria of the genus Bacillus [ 12 , 14 16 , 18 21 , 23 , 26 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glycosylation did not influence pH stability of the XynT6 enzyme. There are data in the literature on pH stability of xylanases; the enzymes that have been studied to date retain no more than 80% of activity after incubation for 1 h in the pH range 5.0–9.6 [ 20 , 21 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the pH stability of Pc Xyn11A in this study was much broader than those reported from A. awamori VTCC-F312 (pH 4.0–8.0) [42], Achaetomium sp. Xz-8 (pH 5.0–10.0) [9], Aspergillus fumigatus MKU1 (pH 4.0–8.0) [45], Bacillus pumilus ARA (pH 5.8–8.2) [46], Bacillus sp. GA1(6) (pH 4.0–7.0) [47] and Penicillium oxalicum (pH 3.0–5.0) [48].…”
Section: Resultsmentioning
confidence: 99%
“…The SDS–PAGE analysis indicated that the recombinant xylanase was expressed at high levels (Fig. A), and the expression level and purification strategy was appropriate for the industrial production of the enzyme . The protein content was 6.47 mg ml −1 , and the specific activity of purified xynB xylanase was 1916 U mg −1 , which was approximately 1.5‐fold higher than xylanase B in A. niger (1250 U mg −1 ) .…”
Section: Discussionmentioning
confidence: 99%